Passport fixing 1 ; Cars Orbos Bill ; The art of mime [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
An investigative report on how fake passports can be bought for a fee; Looks at the high costs of cars and the proposed bill by Congressman Orbos ; Marcel Marceu, a mimist and a legend, a profile of the artist.
Passport fixing 1 (18 min.) -- Cars : Orbos bill (15 min.) -- The Art of mime (13 min.)
VHS.
Keywords: Marceu, Marcel -- Interviews; Passports -- Philippines; Automobiles -- Taxation; Pantomimes